Satisfaction and Opinions for Patients and Nurses regarding Different Types of Bed Bath at Critical Unites - Naglaa Ahmed Ahmed Mohammed ,; Naglaa Gamal Eldien Abdelhafez Hariedy,; Marwa Mohammad Abd Elbaky,; Mona Aly Mohammed, (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2018)
Background: Critical care nurses should ensure that patients’ satisfaction, opinions and needs during bed bath and supported by nursing communication skills, the policies,  dignity and respect for all patients in ICU.Aim of the study: To compare between satisfaction and opinions   for patients and nurses regarding different types of bed bath at critical unites.Design: Comparative descriptive research design. Methods: (60) ICU nurses included in the study assigned to the medical and general ICUs and 60 patients from the previously mention settings. Three tools were constructed to measure  satisfaction and opinions   for patients and nurses regarding different types of bed bath at critical care unites at Assuit University Hospital, EgyptResults: patients satisfaction was 50% with traditional bath and 25% disposable bath and 40% patients positive opinions about traditional bath  and negative opinion 90% in disposable bath. While nurses satisfaction had 6.7% with traditional bath and 33.3% with disposable bath and nurses had 17.6% positive opinions with traditional bath and 76.6% in disposable bed bath. and there was a statistical significance differences with p. value = 0.001Conclusions: the study concluded that patient satisfied and had positive opinion with traditional bed bath while ICU nurses satisfied   and had positive opinions about disposable bed bath.